1994
DOI: 10.1152/ajprenal.1994.267.1.f183
|View full text |Cite
|
Sign up to set email alerts
|

Ca(2+)-dependent activation of T-type Ca2+ channels by calmodulin-dependent protein kinase II

Abstract: The T-type Ca2+ channel is unique among voltage-dependent Ca2+ channels in its low threshold for opening and its slow kinetics of deactivation. Here, we evaluate the importance of intracellular Ca2+ (Cai2+) in promoting low-threshold gating of T-type channels in adrenal glomerulosa cells. We observe that 390 nM to 1.27 microM Cai2+ enhances T-type current by shifting the voltage dependence of channel activation to more negative potentials. This Ca(2+)-induced shift is mediated by calmodulin-dependent protein k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…In addition, singlechannel experiments using membrane patches excised from native bovine ZG cells demonstrated that CaMKII is contained within the domain of the excised patch, suggesting that channel regulatory elements are locally contained (19). The present study significantly enhances our understanding of the nature of CaMKII-α 1H channel interactions and the existence of a CaMKII-channel signaling complex.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In addition, singlechannel experiments using membrane patches excised from native bovine ZG cells demonstrated that CaMKII is contained within the domain of the excised patch, suggesting that channel regulatory elements are locally contained (19). The present study significantly enhances our understanding of the nature of CaMKII-α 1H channel interactions and the existence of a CaMKII-channel signaling complex.…”
Section: Discussionmentioning
confidence: 56%
“…CaMKII expression is increased in structural heart disease (17), and inhibition of its activity reduces Ca 2+ current and ameliorates dysfunction (18). In the ZG cell, CaMKII induces a gating shift of α 1H T-type Ca 2+ channels that enables more channels to open at hyperpolarized potentials, enhancing Ca 2+ entry and thus stimulating aldosterone production (19). Although CaMKII regulates both α 1C HVA (16,20,21) and α 1H LVA channels (19,22,23), the molecular basis for these effects in vitro and in vivo remains unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…9 However, compared with fetal I CaT , kinetic characteristics of I CaT in hypertrophied myocytes revealed a hyperpolarized shift in the voltage-dependent activation (Ϫ39.5Ϯ0.8 mV, nϭ7, versus Ϫ22.4Ϯ0.6 mV, nϭ9, for AS and 18-day-old fetal ventricular cells, respectively), 9 and this hyperpolarized shift was insensitive to Ang II. Because Ca 2ϩ calmodulindependent protein kinase II (CaMKII) shifts the activation of I CaT to more negative potentials in adrenal glomerulosa cells, 31 and that CaMKII is upregulated in hypertrophied ventricles from rats, 32 then CaMKII might be responsible for the hyperpolarized shift in I CaT activation in AS cells.…”
Section: Discussionmentioning
confidence: 99%
“…2ϩ -dependent Pathway-AngII has been reported to enhance the T-type Ca 2ϩ current of bovine AZG cells by a Ca 2ϩ -dependent mechanism that includes a leftward shift in the voltage dependence of channel activation, and requires the activation of a Ca 2ϩ /calmodulin-dependent protein kinase (23,25). Experiments were done to determine whether AngII could modulate T-type Ca 2ϩ currents in bovine adrenal cortical cells by the Ca 2ϩ -dependent, but kinase-independent pathway.…”
Section: Angii Does Not Modulate the T-type Ca 2ϩ Current Through The Camentioning
confidence: 99%
“…In bovine AZG cells, AngII enhances the activity of T-type Ca 2ϩ channels through the activation of Ca 2ϩ /calmodulin-dependent kinase II (23)(24)(25). Alternatively, the effective inhibition of bTREK-1 by AngII in whole cell recordings with [Ca 2ϩ ] i strongly buffered to 22 nM using 11 mM BAPTA suggests that AngII may inhibit bTREK-1 by multiple signaling pathways, only one of which is Ca 2ϩ -dependent.…”
mentioning
confidence: 99%